Analisis Dampak Kekurangan Pejabat Fungsional terhadap Pelaksanaan Pengadaan Barang dan Jasa di Kabupaten Humbang Hasundutan - Marpaung, Jogi Yosefat; Ginting, Wiro Oktavius (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Procurement of goods and services is one of the strategic pillars in realizing effective, efficient, and accountable governance. Its successful implementation greatly depends on the availability of professional and proportional Functional Officials for Goods/Services Procurement (PBJ). This study aims to analyze the impact of the shortage of PBJ functional officials on the effectiveness of procurement implementation in Humbang Hasundutan Regency, with a focus on the adequacy of the number and suitability of job levels. This study uses a qualitative descriptive approach with Armstrong's (1980) Human Resource Management theory as the basis for analysis. Data collection techniques were carried out through document studies, observations, and in-depth interviews with stakeholders in the Goods/Services Procurement Work Unit (UKPBJ). Data analysis was carried out in four stages: data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the shortage of functional officials, especially at the Associate Expert level, has various negative impacts, such as overlapping roles, an imbalance in workloads, delays in the procurement process, low budget absorption, and disruption of public services. The imbalance in job distribution also has an impact on weak planning, supervision, and regeneration of procurement human resources. In conclusion, the less-than-ideal functional position structure is a major obstacle to achieving optimal procurement. Therefore, systematic steps are needed, starting from mapping position requirements, fulfilling a balanced formation between levels, to strengthening training and continuous capacity building in order to improve procurement performance at the regional level